1060. Evaluation of ALT at Sustained Virologic Response (SVR) in Patients with Treated Hepatitis C Virus (HCV) Infection. (31st December 2020) - Theppote, Amanda; Nelson, Amy; Stafford, Kristen A; Wilson, Eleanor; Kottilil, Shyam; Kaplan, Roman
Abstract: Background: With the advent of directly acting antiviral agents, HCV cure rates exceed 90% in real world studies with an excellent safety profile, but viral load tests of cure are expensive and may limit access to treatment, especially in resource-limited settings. Elevated alanine aminotransferase (ALT) has been shown to correlate with hepatocellular damage. Few studies have evaluated the use of ALT in direct acting antiviral (DAA) treated HCV patients post-treatment as a marker of treatment success. In this large retrospective cohort study, we evaluated the ability of serum ALT level at SVR to predict treatment outcome. Methods: We collected baseline demographics, treatment characteristics, and outcomes of DAA-treated patients treated between January 2015 through January 2019 in the VA Maryland Healthcare System as standard of care, and patients in federally qualified health centers in Washington, DC treated between May and November 2015 in the ASCEND study (NCT02339038). Using the ASCEND study as a training set and VA data as the confirmatory set, receiver operating curves (ROC) were generated to determine the predictive value of ALT at SVR for treatment outcome. Results: In total, 1415 patients were included, with 1010 patients from the VA and 405 from the ASCEND cohort. We found 96% (n=1360) of patients achieved SVR; < 4% (n =55) relapsed. Baseline demographics are in Table 1. The ALT at SVR were 21.19 IU/L (SD 13.98) and 17.89 IU/L (SD 11.62) in the VA and ASCEND data, respectively compared to 57.84 (SD 41.06) and 42.53 (SD 19.61) who relapsed. With the VA and ASCEND data combined, the mean ALT at SVR was 20.25 (SD 13.43) in comparison to an ALT of 53.11 (SD 36.33) for those patients who relapsed. ROC analysis revealed that ALT > 22 predicted an increased risk of relapse (Figure 1). Table 1:Characteristics of Subjects Completing Hepatitis C Treatment Figure 1: ROC Curve Conclusion: In this real-world cohort, we found that ALT greater than 22 at SVR corresponded with an increased risk of relapse and was independent of variables previously associated with relapse, including HIV coinfection status, sex, treatment history, and fibrosis staging. Limiting HCV viral load testing to patients with ALT > 22 at SVR may reduce the overall burden of HCV treatment costs for the majority of HCV treated patients. Disclosures: Shyam Kottilil, MD PhD, Arbutus Pharmaceuticals (Grant/Research Support)Gilead Sciences (Grant/Research Support)Merck Inc (Grant/Research Support, Advisor or Review Panel member)